Product market diversification and market emphasis: Impacts on firm idiosyncratic risk in market turbulence. (11th July 2017) - Sun, Wenbin; Govind, Rahul
Abstract : Purpose: Extant literature indicates that increased product market diversification generates both positive and negative impact on firm performance. This inconclusive pattern hinders the decision-making of deploying a firm's resources across different markets. This research aims to embed diversification into a moderation-based framework and demonstrates the conditions under which increased diversification produces either beneficial or harmful effects on firm outcomes. The authors introduce another market configuration dimension, viz., market emphasis, and reveal how changes in diversification and in emphasis yield interactive effects on an important firm performance indicator, idiosyncratic risk. An additional moderator, market turbulence, is also incorporated to further enrich the model in a three-way interaction. Results show that when market turbulence is high, and a firm highly skews its resources to some of its markets, diversifying into more market domains will increase firm idiosyncratic risk. A better choice during increased diversification is to evenly emphasize each of its markets. However, in a market displaying low turbulence, the high diversification-high emphasis pattern may be preferred because of lower firm risk. Design/methodology/approach: To test the hypotheses, the authors collected a comprehensive archival data that contained a large group of public traded US-based manufacturing companies from three different resources. These were the Compustat Annual Database, the Center for Research in Security Prices database and Compustat Business Segment Database. These databases and the combinatorial approach are widely adopted in marketing and management research involving firm strategies and financial outcomes. Findings: When market turbulence is high, simultaneously increasing market diversification and emphasis will more strongly raise firm idiosyncratic risk. However, polarizing into either diversification or emphasis reduces firm risk. When in a low turbulence market, expanding to more product markets and simultaneously emphasizing key markets will decrease idiosyncratic risk. One noticeable fact is that irrespective of whether a firm is in high or low turbulence conditions, choosing a diversification strategy always decreases firm risk when market emphasis is low. However, the impact of this effect however is higher when turbulence is greater. The authors also present the boundary conditions under which the three-way interaction holds. Research limitations/implications: First, the extension to the utilization of idiosyncratic risk stretches the understanding of effective ways of reducing firm risks from an angle of marketing management. This view of firm risk also contributes to further analysis of shareholder value. Classic corporate asset valuation focuses more on the financial performance indicators as well as the firm's strategic domains. This research thus provides a unique and meaningful guideline for the corporate valuation approach from the angle of analyzing the firm's business segment scope and emphasis in the context of the environment. Practical implications: The idea about how many product markets a firm should enter is always one of the primary decisions that contain significant trade-offs. This makes the managers choice difficult during the decision-making processes. The authors suggest that managers should not only consider the scope of product markets but also think carefully about the resources allocated toward each segment. A matrix with dimensions of diversification and emphasis can be explicitly studied during the strategy formulation. The individual blocks within this matrix may have significant outcome differences. Originality/value: Previous research focuses on either a firm's internal assets or external competitive situations when researchers seek the drivers of risk-reduction. This research extends this horizon by adding the interplay between a set of fundamental firm decision areas, diversification and emphasis and the external conditions facing a firm (turbulence).